Romantic Hermeneutic Schleiermacher and Relevance with Existence of Radio Broadcasting - Anam, Rifqi Khairul (Gerakan Indonesia Kita, 2024)
Hermeneutics is defined as the process of interpreting a text. One of hermeneutics school is romantic hermeneutics. Romantic hermeneutics have inquiry to recapturing the truth from the text, which was intended for the writing purpose of the artist. To achieve a genuine, definitive comprehension of a text, it is necessary to provide a psychological interpretation that is a projection into the creative process and the author's subjectivity, thereby bringing the grammatical interpretation of the text closer to a meanings framework based on selected words. The current investigation will concentrate on the romantic hermeneutic and its correlation with the existence of radio. This research is a philosophical reflection approach to library research. The result is in the context of listen radio, the listener interprets a spoken word that is generated by a broadcaster, which is characterized by grammatical arrangement, linguistics, and principles. In the process of intrepretation, the text presented by the broadcaster was interpreted by the listener in the social and cultural context.